EP520 Comparison of different preoperative biopsy techniques in endometrial cancer. (1st November 2019) - Forte, S; Arrigoni, G; Ferrari, F; Coppola, MC; Sartori, E; Odicino, F
Abstract : Introduction/Background: To assess the agreement for histology and grading, between endometrial biopsy and final diagnosis in patients with endometrial cancer, performed with different biopsy techniques. Methodology: We performed a retrospective analysis of patients with endometrial cancer and we collected demographic and clinical data, type of endometrial biopsy technique (Dilation & Curettage - D&C, diagnostic hysteroscopy and subsequent D&C, office hysteroscopy and operative hysteroscopy), biopsy and final diagnosis pathological characteristics. We evaluated global agreement for histology and grading using Cohen's Kappa and we performed subgroup analysis based on the biopsy technique and final grading. Agreement was classified in a five stepfashion way ranging from good, moderate, sufficient, fair and poor. Results: We found 148 patients. Final histology showed 131 (%) endometrioid cancer; 2 patients (1.4%) were finally diagnosed with atypical hyperplasia, 63 (42.6%) with G1, 46 (31%) with G2 and 37 (25%) with G3. Global agreement for histology was fair (K=0.356; SE 0.081; CI 95% 0.08–0.41; p<0.00), while for grading was moderate (K=0.458; SE 0.051; CI 95% 0.36–0.56; p<0.00). In well differenciated tumor agreement was fair (k=0.389; SE 0.074; CI 95% −0.24–0.53; p<0.00), while in G2 and G3 tumors agreement was respectively moderate (k=0.521; SE 0.074; CI 95% −0.38–0.67; p<0.00) and good (k=0.710; SE 0.068; CI 95% −0.57–0.84; p<0.00). Subgroup analysis revealed fair agreement for D&C (k=0.333; SE 0.156; CI 95% 0.03–0.63; p<0.00), as well as for diagnostic hysteroscopy and subsequent D&C (k=0.334; SE 0.098; CI 95% 0.14–0.53; p<0.00) and for office hysteroscopy (k=0.313; SE 0.156; CI 95% 0.00–0.62; p<0.03). Operative hysteroscopy showed moderate agreement (k=0.535; SE 0.084; CI 95% 0.37–0.70; p<0.000). Conclusion: Operative hysteroscopy is the best technique for endometrial biopsy in case of suspected endometrial cancer. Disclosure: Nothing to disclose.